2017
DOI: 10.1158/1940-6207.capr-16-0180
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Multifaceted Chemopreventives in the Suppression of the Oral Squamous Cell Carcinoma (OSCC) Tumorigenic Phenotype

Abstract: Over 1/3 of patients who have undergone oral squamous cell carcinoma (OSCC) surgical resections develop life-threatening and often untreatable recurrences. A variety of drugs, intended for management of recurrent or disseminated cancers, were designed to exploit cancer cells’ reliance upon overexpressed receptors and gratuitous signaling. Despite their conceptual promise, clinical trials showed these agents lacked efficacy and were often toxic. These findings are consistent with evasion of pathway-targeted tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 50 publications
4
25
0
Order By: Relevance
“…Due to low animal numbers statistical analyses were not suitable). The efficacy of 4HPR-PLGA millicylinder in these studies served as proof of concept for more comprehensive studies which showed that 4HPR was effective in combination with other chemotherapeutic agents such as tocilizumab and 2-methoxyestradial at reducing rate of tumor growth (Mallery et al, 2017). Shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to low animal numbers statistical analyses were not suitable). The efficacy of 4HPR-PLGA millicylinder in these studies served as proof of concept for more comprehensive studies which showed that 4HPR was effective in combination with other chemotherapeutic agents such as tocilizumab and 2-methoxyestradial at reducing rate of tumor growth (Mallery et al, 2017). Shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies from our labs have demonstrated that fenretinide (4HPR) inhibits focal adhesion kinase-extracellular matrix (FAK-ECM) interactions and significantly reduces invasion, which is the ultimate step in OSCC development (Han et al, 2015). To address OSCC’s redundant signaling cascades, secondary OSCC chemoprevention will ultimately require complementary agents (Mallery et al, 2017). Based on 4HPR’s multiple mechanisms of action including growth regulation and suppression of gratuitous signaling, (Han et al, 2015) it is our intention to include 4HPR in the secondary chemopreventive formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Also, nutrients appear to be able to influence different cellular processes [9], some of which are related to tumorigenesis [43]; therefore, one consideration is how certain nutrients have an influence on cancer development or progression [44,45]. Natural nutrients are able to disrupt tumorigenesis at multiple ‘omic’ levels and, concurrently, increase the chemotherapeutic efficacy and reduce the side effects related to these treatments [46]. One of the relevant examples is related to oral cancer, which can be arguably prevented by maintaining good oral hygiene, eliminating the use of tobacco and alcohol products, and by having a balanced healthy diet.…”
Section: Cancer Risk Represents a Sum Of Complex Interactions Of Ementioning
confidence: 99%
“… 3 Due to its ability to inhibit inflammation, TCZ is being used in the treatment of rheumatoid arthritis, including as monotherapy, and Crohn disease, asthma, and Coleman disease, and as an adjuvant for multiple myeloma, some lymphomas, and solid-organ cancers, including colorectal, breast, prostate, ovarium, pancreas, lung, and kidney cancers. 4 Recently, TCZ has been used as palliative treatment for oral squamous cell carcinomas 5 , 6 and multi-drug-resistant anemia 7 , 8 ; thus, its range of therapeutic applications has increased.…”
Section: Introductionmentioning
confidence: 99%